miR-183-5p-enriched extracellular vesicles promote the crosstalk between hepatocellular carcinoma cell and endothelial cell via SIK1/PI3K/AKT and CCL20/CCR6 signaling pathways - Han, Ye; Gong, Wu-shuang; Xing, Xue-sha; Zhou, Hang; Wang, Xiao-lei; Xu, Yi; Zhou, Xian-li; Xue, Wei-li (Frontiers in Oncology, 2025)
BackgroundThe cancer-related mortality of primary liver cancer ranks third globally, and hepatocellular carcinoma (HCC) is predominant, posing a serious threat to patients’ health. Understanding HCC’s pathogenesis and target molecules is crucial for early diagnosis and prognosis. Extracellular vesicles (EVs) and their carried miRNAs impact tumor progression. This study aims to investigate miR-183-5p in HCC cell-derived EVs on angiogenesis, progression, and metastasis, and provide diagnostic and therapeutic evidence.MethodsqRT-PCR was used to evaluate the expression of miR-183-5p in HCC tissue and plasma EV samples. Contrast-enhanced ultrasound and The Cancer Genome Atlas evaluated its correlation with angiogenesis and prognosis. In vitro, cell counting kit-8 (CCK-8), colony formation, transwell, tube formation, and permeability assays examined the effect of HCC cell-derived EVs on human umbilical vein endothelial cells (HUVECs). Subcutaneous tumor and lung metastasis models in nude mice verified it in vivo effects. RNA sequencing and databases predicted downstream genes and pathways, and dual luciferase and western blotting assays verified binding and activation. Conditioned medium from treated HUVECs was used on HCC cells, and chemokine levels measured. The CCL20/CCR6 axis effect was studied in vitro and in vivo by knocking down CCR6.ResultsThis study revealed the abnormal upregulation of miR-183-5p in both tissues and plasma EVs from patients with HCC, and its association with unfavorable prognosis. In vivo experiments, the promoting effects of miR-183-5p in HCC cell-derived EVs on the progression, metastasis and angiogenesis were verified by employing subcutaneous tumor formation models and lung metastasis models in nude mice. We demonstrated that miR-183-5p in HCC cell-derived EVs induced HUVECs proliferation, migration, angiogenesis and permeability by downregulating SIK1 expression and activating the PI3K/AKT signaling pathway in vitro. Moreover, stimulated HUVECs could secrete the chemokine CCL20 and induce HCC progression and metastasis through the CCL20/CCR6 signal pathway in vitro and in vivo.ConclusionThe findings indicated that miR-183-5p delivered by EVs from HCC cells is crucial in mediating the communication between HUVECs and HCC cells by modulating the SIK1/PI3K/AKT and CCL20/CCR6 signaling pathways, and EVs-miR-183-5p might be a potential therapeutic target for HCC patients.